No Country for Old Banking: Acceptance Index for Online Banking in China - Lee Yeh, Po Chun (2021)
Multiple indicators that affect Online Banking in China are explored in this study, namely social factors, customer preferences, and online banking factors. An artificial neural network model was performed on data that comprised of online surveys given to small business, commercial bank executives and bank customers. Our results show that attitude towards account security, understanding advantages of online banking, customer credit risk assessment and attitude of the customer towards the credit and risk information system lead to more acceptance of online banking. Neural impact direction results show that customers are more accepting of online banking if there is more account security, more convenience, lower risk for customers, and more developed credit surveillance system. While least important are phone applications, supplementary functions, and how online banking is regulated and operated.